Implication of applying iterative reconstruction on Low Contrast Detectability in CT brain examination. (November 2021) - Kayun, Z.; Karim, M.K.A.; Muhammad, N.A.; Aljewaw, O.B.; Chew, M.T.; Harun, H.H.
Abstract: Iterative reconstruction (IR) of CT images makes it possible to reduce image noise while reducing radiation exposure. There are several impacts of IR techniques on image quality that were not definable when applied to CT head examination. In this study, we aim to evaluate the signal to noise ratio (SNR) and contrast to noise ratio (CNR) of CT brain examination as image quality performance and to establish indicators for image quality as optimization references. Thirty patients, aged ranged from 18 to 65 years old (55.50 ± 21.45) and had CT brain examinations within the period between June 2019 and September 2019 were recruited. The CT examinations were performed using a 128-slices CT-Scanner (Philips Brilliance iCT, Netherland) with standard scanning acquisition protocols of CT brain examinations. Patients were scanned in the helical mode with different scanner settings for the brain and reconstructed using Filtered Back Projection (FBP) and different levels of IR algorithm (iDose 4 level 1 to 5). Objective image quality analysis was performed with a SNR and CNR by drawing region of interest (ROI) on the lens, pons, frontal lobe and cerebellum. Objective measurement shows an overall increase in SNR and slightly increase the CNR at a higher iDose 4 level. Different levels of iDose 4 affect the quality of an objective image in a CT brain exam. IR has great potential to improve CT performance: the image quality of the brainstem and cerebellum are improved, and the dose exposure can be lowered in the future through a prospective study. Highlights: A significant improvement of SNR and CNR with increasing IR level. CTDIvol is found higher than previous studies. SSDE is a promising dose descriptor in CT examination. Noise reduction is proportional with strength of the IR level. Further dose reduction strategy is essential for optimization in CT-Brain examination.